Francisella tularensis Subspecies holarctica in Stranded Beluga Whales, Cook Inlet, Alaska, USA - Natalie Rouse; Jeremy Buttler; Kristy Pabilonia; Christina Weller; Laurel Respicio-Kingry; Elizabeth Dietrich; Jeannine Petersen; Ganna Kovalenko; Eric Bortz; Kathy Burek Huntington (Emerging Infectious Diseases)
We report fatal tularemia in stranded beluga whales in Cook Inlet, Alaska, USA. Francisella tularensis was detected by nanopore metagenomics, confirmed by quantitative PCR and immunohistochemistry, and characterized as F. tularensis subspecies holarctica by multilocus sequence typing. Our findings should be considered when assessing biosecurity and marine mammal health in the North Pacific.